Long-term monitoring of size and feeding of resident yearlings of threespine stickleback (leiurus morph) in the littoral zone of Lake Azabachye (Kamchatka River basin) - V. F. Bugaev; T. L. Vvedenskaya (Известия ТИНРО, 2018)
Resident morph of threespine stickleback Gasterosteus aculeatus is an important competitor for food for sockeye salmon juveniles in their freshwater period of life. The most intense feeding interactions occur in the pelagic zone of lakes between sockeye salmon underyearlings and yearlings of resident threespine stickleback. To evaluate this factor, the size and feeding were monitored for the resident yearlings of threespine stickleback (leiurus morph) in the littoral zone of Lake Azabachye annually on July 1 (±1 day) since 1985 (in late July — early August these yearlings migrate in mass to the pelagic zone of the lake). The mean body length varied from year to year between 29.02 ± 0.19 — 40.52 ± 0.33 mm, with some periodicity of 8–9 — 12 years presumably caused by environmental changes. Their main prey was chironomids, with average percentage in the food bolus 44.3 % (from 3.3 % in 2011 to 79.2 % in 2008). The mean stomach fullness of leiurus at the age 1+ varied by years in the range 27.8–254.5 ‱ and correlated significantly with year-to-year changes of the water temperature in the lake; the specimens with empty stomach were absent and the highest individual index reached 527.9 ‱. The consumption was the highest in 2011 and 2017 (mean indices of stomach fullness 215.7 and 254.5‱, respectively). Sockeye underyearlings were almost absent in the littoral zone in the period from late June to middle July.